ABTS radical scavenging and antimicrobial activities of flavonoid fractions from Terminalia bellirica fruit rinds - James, Jesna; Soumya, K; Archana, T. M; Shahid, A.P; Sudheesh, S (Journal of Drug Delivery and Therapeutics, 2019)
Plants are widely used in traditional medicine from the beginning of mankind because of its significant healing power and least side effects. The extraction and isolation of biologically active components from plants for the designing and synthesis of novel drugs became an emerging research area for years. Plants possess a large spectra of secondary metabolites such as flavonoids, tannins, terpenoids, alkaloids, phenolic acids etc. they are the major contributors of pharmacological activities shown by plants. Present study aimed at the ABTS radical scavenging and antimicrobial testing of flavonoid fractions from the fruit rinds of Terminalia bellirica. The effect of flavonoids from diethyl ether and ethyl acetate extracts against six bacterial strains and two fungal strains are evaluated by the agar well diffusion method. The results revealed that these flavonoid containing fractions possess excellent ABTS radical scavenging activity with very low concentrations and considerable antimicrobial potential when compared with their respective standards. Keywords: ABTS radical, antimicrobial, diethyl ether, ethyl acetate, flavonoid, Terminalia bellirica